2020
DOI: 10.1136/bmjopen-2020-040664
|View full text |Cite
|
Sign up to set email alerts
|

Ideal cardiovascular health in urban Jamaica: prevalence estimates and relationship to community property value, household assets and educational attainment: a cross-sectional study

Abstract: ObjectiveIdeal cardiovascular health (ICH) is associated with greater longevity and reduced morbidity, but no research on ICH has been conducted in Jamaica. We aimed to estimate the prevalence of ICH in urban Jamaica and to evaluate associations between ICH and community, household, and individual socioeconomic status (SES).DesignCross-sectional study.SettingUrban communities in Jamaica.Participants360 men and 665 women who were urban residents aged ≥20 years from a national survey, the Jamaica Health and Life… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(27 citation statements)
references
References 51 publications
2
22
0
Order By: Relevance
“…A recent NCD model of care review in sub-Saharan Africa also revealed that leveraging existing human resources, decentralization of NCD care to primary health facilities, task redistribution including to lay health cadres, designing patient-centered quality of care, and continued training and mentorship are key to successes of NCD treatment and control [24]. Although community screening and sensitization on the need for NCD care is critical, strategies are needed to ensure better linkage and retention into care [17].…”
Section: Discussionmentioning
confidence: 99%
“…A recent NCD model of care review in sub-Saharan Africa also revealed that leveraging existing human resources, decentralization of NCD care to primary health facilities, task redistribution including to lay health cadres, designing patient-centered quality of care, and continued training and mentorship are key to successes of NCD treatment and control [24]. Although community screening and sensitization on the need for NCD care is critical, strategies are needed to ensure better linkage and retention into care [17].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, data from JHLS-III found that among urban participants only 52% were classified as having a low salt diet, defined as no added salt at the table and infrequent consumption of processed foods. 25 In keeping with the recommendations of WHO and PAHO and consistent with Caribbean Community (CARICOM) recommendations and a mandate of the Ministry of Health and Wellness in Jamaica, we propose the implementation of a national salt reduction program in order to reduce blood pressure and associated CVD. The program will be aligned with the overall Ministry of Health's National Strategic and Action Plan for Prevention and Control of Non-Communicable Diseases (NCDs) and the mandate of the Food Industry Task Force.…”
Section: Introductionmentioning
confidence: 90%
“…3 Some details on the procedures used in JHLS-III have been published. 25 The survey enrolled a nationally representative sample of Jamaicans 15 years and older using a multi-stage sampling design. In the first stage, 171 enumeration districts (EDs) were randomly selected from a national total of 6,241 EDs, with selection probability proportionate to the size of the ED.…”
Section: Component 1: Spot Urine Sodium Analyses Data Sourcesmentioning
confidence: 99%
“…We conducted a cross-sectional analysis of data collected as part of the Jamaica Health and Lifestyle Survey 2016-2017 (JHLS-III), a national health examination survey conducted between September 2016 and February 2017. Details of the procedures used in JHLS-III and the protocol for this study have been published previously (24, 25). In brief, trained personnel were engaged to collect data on a wide cross-section of health-related indices using interviewer-administered questionnaires, physical measurements, point-of-care and laboratory measurements and geographic information system (GIS) mapping.…”
Section: Methodsmentioning
confidence: 99%